Water barriers in the Holy Quran a semantic study (Journal of the College of Basic Education, 2023)
Human science has graduated to know the facts about the difference in sea waters and the barriers between them that preserve the distinctive characteristics of each sea in terms of density, salinity, aquatic life, temperature, and others. In this research, I have tried to reveal the linguistic, explanatory, scientific and miraculous significance of these barriers, by studying them in three demands. And I reached several results that I mentioned in the appropriate place in this research, and God is the Grantor of success.